2017
DOI: 10.1186/s12967-016-1109-0
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of the intradiscal implantation of stromal vascular fraction plus platelet rich plasma in patients with degenerative disc disease

Abstract: BackgroundStromal vascular fraction (SVF) can easily be obtained from a mini-lipoaspirate procedure of fat tissue and platelet rich plasma (PRP) can be obtained from peripheral blood. The SVF contains a mixture of cells including ADSCs and growth factors and has been depleted of the adipocyte (fat cell) population. We evaluated the safety and efficacy of administering SVF and PRP intra-discally into patients with degenerative disc disease.MethodsA total of 15 patients underwent a local tumescent liposuction pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 16 publications
3
91
0
2
Order By: Relevance
“…39,40 The mesodermal cell population, defined as SVF, is typically harvested by enzymatic digestion and centrifugation, and contains a heterogeneous array of cell types, including mesenchymal stem cells, endothelial cells, perivascular cells, fibroblasts, and immune cells. 41,42 SVF has gained increased popularity and has wide applicability in the regeneration of the spinal cord, 43 intervertebral disc, 44 and cartilage. 45,46 However, most SVF were directly injected into the target tissues or generated into pellets for implantation without in vitro expansion.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 The mesodermal cell population, defined as SVF, is typically harvested by enzymatic digestion and centrifugation, and contains a heterogeneous array of cell types, including mesenchymal stem cells, endothelial cells, perivascular cells, fibroblasts, and immune cells. 41,42 SVF has gained increased popularity and has wide applicability in the regeneration of the spinal cord, 43 intervertebral disc, 44 and cartilage. 45,46 However, most SVF were directly injected into the target tissues or generated into pellets for implantation without in vitro expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding prospective trials, the results were positive for PRP, with pain outcomes improving in the majority of PRP‐treated patients . Notably, the Comella et al study used a combination of stromal vascular fraction (SVF) and PRP for their injectate; SVF is a combination of ADSCs and growth factors.…”
Section: Orthobiologics and The Literaturementioning
confidence: 99%
“…Regarding prospective trials, the results were positive for PRP, with pain outcomes improving in the majority of PRP-treated patients. 41,42 Notably, the Comella et al study used a combination of stromal vascular fraction (SVF) and PRP for their injectate; SVF is a combination of ADSCs and growth factors. The remaining prospective PRP study found 47% of patients had a greater than 50% improvement in VAS scores and a 30% decrease in Oswestry Disability Index (ODI) scores at 6 months.…”
Section: Discogenic Orthobiologic Studiesmentioning
confidence: 99%
“…The SVF has already been used in Achilles tendinopathy treatment, breast reconstruction, and other treatments in clinical trials 25,26 . Comella et al treated patients with IVD degeneration by intradiscal implantation of SVF plus platelet-rich plasma, and a majority of patients reported improvements in several parameters, including flexion and pain rating 27 . However, the isolation of the SVF by traditional methods such as collagenase does not bode well with regulatory authorities 28 .…”
Section: Introductionmentioning
confidence: 99%